For the Money or the Thrill of the Game: The Financial Performance of National Basketball Association Arena Sponsors - Brian Nichols; Joey Smith (Journal of Accounting, Business and Management (JABM), 2022)
Companies that sponsor NBA arenas spend millions of dollars each year for the naming rights. To our knowledge, no studies have examined the financial performance of the sponsoring companies over the course of the sponsorship. Managers appear to believe that such expenditures generate net financial benefits for their companies; however, measuring such returns can be elusive. We examine the impact of sponsorship on sales growth and stock price returns before, during, and (if applicable) after the sponsorship of the sponsoring companies. We then explore if the following factors moderate or enhance the sponsorship results – the NBA team’s on-court performance during the regular season, the performance during the playoffs, and whether the sponsor’s corporate headquarters are co-located with the arena. We find evidence of negative sales growth associated with sponsorships, but if the NBA team makes the playoffs, that performance positively correlates with the sponsoring company’s stock price return.